Association betweenMaternal Age at Pregnancy, Socioeconomic Status, Physical Environment, Prenatal, Perinatal, Postnatal History, and the Risk of Mental Retardation - Nurochim, Erna; Indarto, Dono; Prayitno, Adi (Journal of Maternal and Child Health, 2016)
Background: Mental retardation (MR) is a serious public health problem for an country. The prevalence of mental retardation in Indonesia was estimated at 1-3% of the population. About 0.1% of whichneed treatment and guidance the whole life. This study aimed to determine the association between maternal age at pregnancy, socioeconomic status, physical environment, prenatal, perinatal, postnatal history, and mental retardation.Subject and methods: This was an analytic observational study with case control design. This study was conducted in Pare, Kediri, East Java, Indonesia,from October to December 2016. A total 105 study subjects, consisting of 35 MR cases and 70 controls were selected for this study by fixed disease sampling. The independent variables were maternal age at pregnancy, socioeconomic status, physical environment, prenatal, perinatal, and postnatal history. The dependent variable was mental retardation. The data were collected by questionnaire and analyzed by logistic regression model.Results: Maternal age Ã¢â°Â¥35 years at pregnancy was associated with an increased risk of MR, and it was statistically significant The result showed that motherÃ¢â¬â¢s age while pregnant (OR=10.18; 95%CI=2.77 to 37.39; p<0.001). High socioeconomic status (OR=0.23;95%CI=0.07 to 0.81; p=0.022), good physical environment (OR=0.13; 95%CI=0.04 to 0.45; p=<0.001), good prenatal history (OR=0.24;95%CI=0.07 to 0.82; p=0.022), good perinatal history (OR=0.45;95%CI=0.15 to 1.40; p=0.168), good postnatal (OR=0.43;95%CI=0.14 to 1.35; p=0.148), were associated with a decreased risk of MR. Nagelkerke R2=53.8% for this model.Conclusion: Maternal age Ã¢â°Â¥35 years at pregnancy increases the risk of MR. High socioeconomic status, good physical environment, good prenatal, perinatal, and postnatal history, decrease the risk of MR.Keywords: mental retardation, maternal age at pregnancy, socioeconomic status, environment, pregnancy history.Correspondence:ÃÂ Erna Nurochim. Masters Program in Public Health, Sebelas Maret University, Surakarta.Journal of Maternal and Child Health (2016), 1(2): 119-130https://doi.org/10.26911/thejmch.2016.01.02.07